An Exploration of Female Identity in Textbooks from the Spanish Transition to Democracy between Continuity and Change - Delgado Granados, Patricia; Heras Monastero, Bárbara de las (Espacio, tiempo y educación, 2024)
School textbooks constitute an important tool in terms of the transmission of models of social behaviour, values and cultural norms among the school-age population. This article aims to analyse the process of constructing female identity in secondary school textbooks during the Spanish transition to democracy (1975-1982). In order to achieve this objective, a sample of thirty textbooks corresponding to History, Geography, Language and Literature in the BUP (High School Education) and COU (University Foundation Course) stages established by the General Education Act of 1970 has been selected. To facilitate their study, we have employed a combination of historical-educational methodology from a perspective of gender and critical discourse analysis by way of the implementation of the qualitative software Nvivo version 12. The results obtained demonstrate two contrasting models of female identity that underpin the school textbooks corresponding to this period: one traditional and one modern. Both models – based on discourses, images and cultural representations, outlined and articulated the identity construction among the school population. With the arrival of democracy, minor progress can be observed in relation to visibility and the active presence of women. However, sexist stereotypes associated with traditional gender roles that are presented more subtly as a result of the requirements of the political, social and educational context, persist.